KONFLIK KEWENANGAN ANTARA PENGADILAN NEGERI DAN PENGADILAN AGAMA DALAM MENANGAI PERKARA SENGKETA WARIS ORANG ISLAM - Ilham Thohari (LPPM IAIN Kediri, 2015)
This article aims at discussing about a lawsuit of authority between a state court and a religion court related to authorities to receive, investigate, and decide a lawsuit of heir among Muslim. In this article, it is explained that receiving, investigating, and deciding a lawsuit of heir among Muslim are not absolutely the authorities of the religion court, but the state court also has these authorities. It is based on (1) The Law number 2, 1986 jo Stbl. 1937 number 116, the article 50 which states that the state court has duty and authority to investigate, decide, and solve criminal and civil cases in the fi rst level, and (2) the explanation of The Law number 3, 2006, article 49 about the religion court which states that the meaning of among Muslim is included people or companies which voluntarily follow Islamic law. Therefore, it can be conclude that the religion court has authorities to receive, investigate, and decide a lawsuit of heir among Muslim if they voluntarily follow the Islamic law, and the state court has authorities to receive, investigate, and decide a lawsuit of heir among Muslim if they do not voluntarily follow the Islamic law.